PENGARUH PERMAINAN CROSSWORD PUZZLE TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK SD IT HARAPAN UMAT PURBALINGGA - Rokhayati, Tri; Taniredja, Tukiran; Jazuli, Akhmad (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2020)
This research purpose to knowing affected of: 1) crosswords puzzle learning to learning motivation at third class in Harapan Umat Elementari School IT Purbalingga, 2) Crosswords puzzle learning to learning result at third class. Research method was experiment, with two group treatments that were control group and experiment group. Group control was 3C class and experiment group was 3F class. Data using in this research were primary and secondary data. And then data be analyzed by Independent Sample t-test. Result of the research have shown: 1) crosswords puzzle learning significant affected to learning motivation at third class in Harapan Umat Elementary School IT Purbalingga; and 2) crosswords puzzle learning affected to learning result at third class.